A 'delivery-democracy dilemma'? Mapping and explaining policy change for public engagement with energy infrastructure. Issue 4 (4th July 2018) - Cowell, Richard; Devine-Wright, Patrick
ABSTRACT: Understanding how governments orchestrate public engagement in energy infrastructure decisions has important implications for the relationship between energy transitions, democracy and justice, but existing research is deficient in focusing mainly on single case studies. In response, we conduct a multi-sectoral, comparative analysis for the first time to assess how UK governments have engaged publics, applying a novel mapping methodology that is systematic, longitudinal and cross-technology. Moreover, our focus embraces mechanisms of consultation and support measures (e.g. community benefits) and seeks to explain patterns of change using a pragmatist sociology framework. Findings indicate trends towards a reduced scope for public engagement alongside expanded encouragement of community benefits, but also important sectoral differences. On-shore wind moved towards giving local decision-makers significant control over decisions. Gas-fired power stations experienced continuity, with central government controlling consents and limited interest in community benefits. Fracking facilities received intense promotion of community benefits, alongside incremental moves to restrict local decision-making. We argue that the patterns observed reflect government beliefs about the scope for depoliticisation in concrete situations, in which the conjunction of technologies, sites and publics affects how and whether arrangements for public engagement change. These results raise challenges for how researchers seek to connect energy transitions and democracy.